Temporary Waqf as a Study of Fiqh Muamalah (Juridical Thoughts and Possibility of Its Implementation) - Solichin, Nur Mifchan (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2022)
Abstract: Based on data from the Indonesian Waqf Board (BWI), Indonesia has a waqf potential of IDR 180 trillion per year. However, waqf in Indonesia has not been fully managed effectively, in many cases there are abandoned waqf objects that are not maintained. To reduce the abandonment of waqf assets, the discourse of waqf fiqh has developed with the discussion of temporary waqf. The question that arises is what is the opinion of the fiqh scholars about temporary waqf, especially the scholars of the four madzhabs; Shafi'i, Hanbali, Hanafi and Maliki? Then how is the possibility of implementing the temporary waqf? This research is a combination of normative and empirical, using a qualitative approach, by researching the law on temporary waqf, supported by empirical data. Primary data is obtained from field research, in the form of interviews with the Head of the Waqf and Land Institute of the Nahdlatul Ulama Regional Board of Yogyakarta Special Region. Secondary data is obtained from fiqh books, articles and regulations in Indonesia regarding temporary waqf. Shafi'iyah and Hanabilah scholars such as As-Shirāzi and Ibn Qudamah rejected the practice of temporary waqf. On the other hand, the Hanafiyah and Malikiyah allow temporary waqf. Nahdlatul Ulama officially recognises four schools of fiqh: Hanafi, Maliki, Shafi'i, and Hanbali, so there is a possibility that temporary waqf can be implemented by Nahdlatul Ulama because Hanafiyah and Malikiyah permit temporary waqf.